UAV - Red Green Blue (RGB) Orthomosaic from Röbäcksdalen Drone area 01 from 2021 - Röbäcksdalen Field Research Station (Swedish University of Agricultural Sciences, 2023)
Near-ground RGB orthomosaics collected from UAV platforms, by means of RGB cameras containing red, green and blue bands. Nominal pixel resolution is 5 cm.
Röbäcksdalen Field Research Station (2023). UAV - Red Green Blue (RGB) Orthomosaic from Röbäcksdalen Drone area 01 from 2021, 2022-07-18 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Z2LGX-uM6aeANYB-finwAtUY
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap